VisTrails Home

User:Tohline/Math/EQ Toroidal04

From VisTrailsWiki

< User:Tohline(Difference between revisions)
Jump to: navigation, search
(Created page with '<table border="0" cellpadding="5" align="center"> <tr> <td align="right"> [[Image:LSU_Key.png|25px|link=http://www.vistrails.org/index.php/User:Tohline/Appendix/Equation_templat…')
 
(2 intermediate revisions not shown)
Line 3: Line 3:
<tr>
<tr>
<td align="right">
<td align="right">
-
[[Image:LSU_Key.png|25px|link=http://www.vistrails.org/index.php/User:Tohline/Appendix/Equation_templates#Special_Function_Relationships]]
+
[[Image:LSU_Key.png|25px|link=http://www.vistrails.org/index.php/User:Tohline/Appendix/Equation_templates#Relationships_Between_Various_Associated_Legendre_Functions]]
</td>  
</td>  
   <td align="right">
   <td align="right">
-
<math>~Q_\nu^\mu(z)</math>
+
<math>~(\nu - \mu + 1)P^\mu_{\nu + 1} (z)</math>
   </td>
   </td>
   <td align="center">
   <td align="center">
Line 13: Line 13:
   <td align="left">
   <td align="left">
<math>~
<math>~
-
e^{i \mu \pi} ~ (2\pi)^{-\frac{1}{2}} (z^2-1)^{\mu/2} ~\Gamma(\mu + \tfrac{1}{2})~\biggl\{
+
(2\nu + 1)z P_\nu^\mu(z) - (\nu + \mu)P^\mu_{\nu-1}(z)
-
\int_0^\pi (z - \cos t)^{-\mu - \frac{1}{2}} \cos[(\nu + \tfrac{1}{2})t] ~dt
+
-
-\cos(\nu\pi) \int_0^\infty (z + \cosh t)^{-\mu - \frac{1}{2}} e^{-(\nu + \frac{1}{2})t} ~dt
+
-
\biggr\}
+
</math>
</math>
   </td>
   </td>
</tr>
</tr>
<tr>
<tr>
-
   <td align="center" colspan=4>
+
   <td align="center" colspan="4">
-
[https://authors.library.caltech.edu/43491/1/Volume%201.pdf A. Erd&eacute;lyi (1953)]:&nbsp; Volume I, &sect;3.7, p. 156, eq. (10)  
+
[https://books.google.com/books?id=MtU8uP7XMvoC&printsec=frontcover&dq=Abramowitz+and+stegun&hl=en&sa=X&ved=0ahUKEwialra5xNbaAhWKna0KHcLAASAQ6AEILDAA#v=onepage&q=Abramowitz%20and%20stegun&f=false Abramowitz &amp; Stegun (1995)], p. 334, eq. (8.5.3)
   </td>
   </td>
</tr>
</tr>
Line 30: Line 27:
<tr>
<tr>
   <td align="right">
   <td align="right">
-
NOTE:  Both <math>~P_\nu^\mu</math> and <math>~Q_\nu^\mu</math> satisfy this same recurrence relation.
+
NOTE:  <math>~Q_\nu^\mu</math>, as well as <math>~P_\nu^\mu</math>, satisfies this same recurrence relation.
   </td>
   </td>
</tr>
</tr>
</table>
</table>

Current revision as of 14:39, 1 July 2018

~(\nu - \mu + 1)P^\mu_{\nu + 1} (z)

~=

~
(2\nu + 1)z P_\nu^\mu(z) - (\nu + \mu)P^\mu_{\nu-1}(z)

Abramowitz & Stegun (1995), p. 334, eq. (8.5.3)

NOTE: ~Q_\nu^\mu, as well as ~P_\nu^\mu, satisfies this same recurrence relation.

Personal tools